Health Education for the Prevention of Hypertension in Elderly RW 11 Jayagiri Village, Lembang District, West Bandung Regency - Sianipar, Imelda Martina G; Ardayani, Tri; Tresnadjaja, Reynaldi; Sinaga, Anni; Sujana, Treesia; Hariningsih, Wintari (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
The purpose of this activity is to plan community service activities to solve problems obtained based on situation analysis on problem prioritization by providing health education to the community to always maintain health. The method used consists of preparation, implementation, and closing. The implementation was carried out by means of counseling which took place at the RW 11 mosque, Jayagiri Desara Village, Lembang District, West Bandung Regency, which was attended by 36 participants and could be carried out well and smoothly and conducive from the beginning to the end of the activity. The results obtained are that the community's understanding of the meaning, causes, symptoms, prevention, treatment, and impact of hypertension has increased. This community service activity is expected to provide tangible benefits to the Jayagiri Village community and become an inspiration for similar efforts in various other areas.